(3fKQ GdoqOqQs - (3efUhQ Hf GdMSjf GdQGRqj, nCHh nSrYO GdBHj,J (B421 (3g` s ((3CMeO Hf Ydj GdcGJH GdHZOGOj s)
(3ChdgG (B:s
(3JfbU ef ChdgG hbjd dg(B: (3gd ef CMmO dG YjH ajg? bGd(B: (3GdPj dG YjH ajg GdPj dG jehJ s
(3BNQgG (B:s
(3Jdc hGddg CNJj dCHj hCej, hgPg CNJ GdQLd dCHjg hCeg Je GdLRA GdNGeS hgh BNQ cJGH fKQ GdoqOqQ s
(3GdLRA GdNGeSs
(3aj GdaUd GdSGHYs
(3hgh GdCNjQ ef GdcJGHs
(3GfXQ aj GdLRA GdChd GQbGe (B851-854 (3COH s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
Keywords: (3GdCOHs